1994
DOI: 10.1152/ajpheart.1994.267.4.h1368
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic activation decreases medium-sized arterial compliance in humans

Abstract: This study used a precise noninvasive method in normotensive humans to determine the effects of sympathetic activation on arterial compliance. A recently developed, high-resolution echo-tracking system capable of measuring systolic/diastolic variations of arterial diameter was coupled to a Finapres system and used to calculate instantaneous systolic/diastolic pressure-diameter and compliance-pressure curves for a muscular medium-sized artery, the radial artery. Two standardized tests of sympathetic system acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
149
1
13

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(169 citation statements)
references
References 0 publications
6
149
1
13
Order By: Relevance
“…Activation of the sympathetic nervous system has been shown to reduce distensibility of small-and medium-size arteries in animals [30,31]. Also, one study demonstrated that increases in sympathetic stimulation are associated with the reduction of radial artery distensibility in humans [33]. The sympathetic nervous system exerts a marked tonic restraint on large arterial distensibility, and this restraint involves large arteries with a predominant elastic structure and arteries with a predominant muscle structure.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the sympathetic nervous system has been shown to reduce distensibility of small-and medium-size arteries in animals [30,31]. Also, one study demonstrated that increases in sympathetic stimulation are associated with the reduction of radial artery distensibility in humans [33]. The sympathetic nervous system exerts a marked tonic restraint on large arterial distensibility, and this restraint involves large arteries with a predominant elastic structure and arteries with a predominant muscle structure.…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic activation during the cold-pressor test or mental stress decreases radial arterial compliance and increases SBP and pulse pressure. 26 The sympathetic nervous system may also contribute to blood pressure levels in the long term by mechanisms other than its effect on vasomotor tone, such as by its effects on the kidney. 27 Wallin et al 28 have demonstrated that in healthy human subjects, resting sympathetic nerve traffic is proportional in sympathetic nerves to both muscle blood vessels and the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…20,50,51 Arterial compliance Loss of AC during sympathetic stimuli leads to exaggerated increases in an a 2 -adrenergic-mediated vasoconstriction and/or decreases in b 2 -adrenergicmediated vasodilation, both of which contribute to increases in arterial stiffness. Augmented and/or exaggerated sympathetic activity has been shown to further reduce distensibility of small, medium and large arteries, [49][50][51][52][53] and is a common denominator for risk factors related to hypertension. [54][55][56] Our prior study, and that of others, has shown that a strong relationship exists between .…”
Section: Baroreflex Sensitivitymentioning
confidence: 99%